Designing marketing strategy using SWOT and Blue Ocean strategy to increase sales and competitiveness at PT Zaga Krida Teknik - Larisang, Larisang; Putri, Meylia Vivi (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The intense competition in the business world forces companies to devise strategies to outperform their rivals. As more businesses target the same market segments, the available market becomes increasingly crowded. To address this challenge, a strategic analysis is essential. This research employs the SWOT method and the Blue Ocean Strategy. The SWOT analysis identifies the company’s strengths, weaknesses, opportunities, and threats, helping to assess its competitive position. Meanwhile, the Blue Ocean Strategy aims to shift from a highly competitive market (Red Ocean) to a new, uncontested market (Blue Ocean). Data analysis results show the need for strategic adjustments. SWOT analysis highlights areas where the company lags compared to competitors, while the Blue Ocean Strategy outlines actions to access untapped markets, increasing product sales. The study reveals that PT Zaga Krida Teknik can escape fierce competition by addressing existing shortcomings and developing unique features. Specifically, the company should introduce three new elements: branded nameplates, employee training, and a website. Additionally, it must improve product quality, promotional activities, and product guarantees. These strategic changes are expected to enhance the company's market position and drive growth.